Twenty Second Meeting of the National Development Council Summary Record New Delhi September 5 and 6, 1965 - Planning Commission (Planning Commission, 1967)
The main policy recommendations as have emerged from the discussions in these Committees are placed before the National Development Council. Suggestions for any modifications in the sectoral allocations have not been included in these recommendations and these have been taken into consideration and incorporated, to the extent possible, in the Draft Outline. On the Rural Manpower Programme, an inter-State Conference was held on April 14-16. 1965. Its recommendations could not be placed before the N.D.C. Committee on Agriculture & Irrigation, but in view of the importance of these recommendations these are also included in this paper. On most of these recommendations action has been initiated. After the N.D.C. has approved these commendations further action will be taken by the concerned agencies, viz., the Planning Commission. Central Ministries and the State Governments.
Summary Record New Delhi September 5 and 6, 1965 Government of India Planning
Government of India Planning Commission
Keywords: Recommendations of the Committees of the National Development Council; Agricultural Research; Improved Seeds; Soil survey organizations; The Ministry of Food & Agriculture; Plant Protection; Land Reclamation; Location of industries; including regional development; Private sector including State participation; Labour Laws and Employment; Indigenous Systems of Medicine